Different teams, same conclusions?: a systematic review of existing clinical guidelines for the assessment and treatment of tinnitus in adults - Fuller, Thomas; Haider, Haula; Kikidis, Dimitris; Lapira, Alec; Mazurek, Birgit; Norena, Arnaud; Rabau, Sara; Lardinois, Rachelle; Cedderoth, Christopher; Edval, Niklas; Bruggemann, Petra; Nemholt, Suzanne; et al. (Frontiers, 2017)
Background: Though clinical guidelines for assessment and treatment of chronic subjective tinnitus do exist, a comprehensive review of those guidelines has not been performed. The objective of this review was to identify current clinical guidelines, and compare their recommendations for the assessment and treatment of subjective tinnitus in adults.